Impact of gastroesophageal reflux disease symptoms on the quality of life in pregnant women: a prospective study. Issue 8 (August 2017) - Fill Malfertheiner, Sara; Seelbach-Göbel, Birgit; Costa, Serban-Dan; Ernst, Wolfgang; Reuschel, Edith; Zeman, Florian; Malfertheiner, Peter; Malfertheiner, Maximilian V.
Abstract : Objective: Pregnant women often suffer from gastroesophageal reflux disease (GERD). GERD symptoms are known to influence the quality of life; however, there is a lack of data in pregnant women. The aim of this study was to establish the impact of GERD symptoms on health-related quality of life (HRQOL) during pregnancy. Participants and methods: A prospective longitudinal cohort study to investigate the impact of GERD symptoms on the HRQOL was carried out in 510 pregnant women and 330 nonpregnant women as controls. Two validated questionnaires, the Reflux Disease Questionnaire and the Quality of Life in Reflux and Dyspepsia Questionnaire, were used. Results: The study showed a significant negative impact on HRQOL in pregnant women with GERD symptoms. All five areas, emotional distress, sleep disturbance, vitality, food/drink problems, and physical/social functioning, were significantly reduced, but the most significant impact was on sleep (Quality of Life in Reflux and Dyspepsia Questionnaire score −35%). Overall, quality of life in women with GERD worsened throughout pregnancy. Conclusion: GERD is frequently seen in pregnant women and has a negative impact on HRQOL, especially in late pregnancy. Therefore, there is a need for adequate therapy of GERD in pregnant women and HRQOL could be an adequate monitoring tool in this population.